2018
DOI: 10.1080/10773525.2018.1500804
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of retrospectively reported seasonality in native and non-native residents of Chukotka and Turkmenistan

Abstract: Seasonality represents a response of human mood, physiology, and behavior to annual variations in natural and social environment. A strong seasonal response is expected in non-native than native residents of such regions as Turkmenistan that is characterized by high air temperature in summer and Chukotka that is characterized by high-amplitude annual variation in both air temperature and day length. Seasonality was retrospectively reported by 732 residents of these regions. Self-reports on sleep-wake traits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Both qualitative and quantitative research linked acute and short-term weather variables such as storms, flooding, temperature, and seasonality with a range of psychological and mental health impacts including depression and anxiety [e.g. 10, 49, 50], suicide [47][48][49], self-harm [50], post-traumatic stress disorder [PTSD; [51][52][53], psychological resilience [53], selfreported mood and behavior [54,55], mental illness and behavioral disorders [56], and strong emotional reactions such as fear and anxiety [e.g . 27].…”
Section: How Does Climate Change Impact Indigenous Mental Health?mentioning
confidence: 99%
“…Both qualitative and quantitative research linked acute and short-term weather variables such as storms, flooding, temperature, and seasonality with a range of psychological and mental health impacts including depression and anxiety [e.g. 10, 49, 50], suicide [47][48][49], self-harm [50], post-traumatic stress disorder [PTSD; [51][52][53], psychological resilience [53], selfreported mood and behavior [54,55], mental illness and behavioral disorders [56], and strong emotional reactions such as fear and anxiety [e.g . 27].…”
Section: How Does Climate Change Impact Indigenous Mental Health?mentioning
confidence: 99%
“…The general pattern includes a winter peak of longer sleep and decreased performance. Reports consistently associate winter months with longer sleep [30][31][32][33][34][35][36][37] and more sleep concerns. 38 An online survey of 2003 adults commissioned by the AASM showed that one-third (34%) of the respondents slept "more than usual" during the winter.…”
Section: Longitudinal Measuresmentioning
confidence: 99%
“…was administered to identify the circadian preference of our participants. MEQ is a 19-item test that also allows subdividing participants into six categories: definitely morning (70-86), moderately morning (59-69), intermediate morning (50-58), intermediate evening (42-49), moderately evening(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and definitely evening(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Similar responses have been found in our own species. For instance, as was documented in a study of month-to-month variation in sleeping problems [ 14 , 15 ], more than one-half of native residents and newcomers to a region with hot summer temperatures reported a rise in the prevalence of each of the studied symptoms of sleep disturbance in the summer months (e.g., increase of complaints about daytime sleepiness, difficulties falling and staying asleep, and premature awakening). In the present study of fruit fly, we found that a more promising marker of infertility might be hypersomnia in any of two temperature conditions and an impaired responsiveness of the sleep-wake behavior to stressful levels of temperature.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, a strong annual rhythmicity of sleeping problems has been reported by both newcomers and native residents of a region with hot summer temperature. Even people exposed at high latitudes to very cold winter temperatures and extremely variable photoperiod reported less profound seasonality [ 14 ]. In the absence of air conditioning, summer season was found to be associated with a drastic increase of any of several studied symptoms of sleep disturbance, including daytime sleepiness, premature awakening, and difficulties falling and staying asleep [ 15 ].…”
Section: Introductionmentioning
confidence: 99%